Modulation of radio frequency signals by ULF waves - C. L. Waters; T. K. Yeoman; M. D. Sciffer; P. Ponomarenko; D. M. Wright (Annales Geophysicae, 2007)
The ionospheric plasma is continually perturbed by ultra-low frequency (ULF; 1–100 mHz) plasma waves that are incident from the magnetosphere. In this paper we present a combined experimental and modeling study of the variation in radio frequency of signals propagating in the ionosphere due to the interaction of ULF wave energy with the ionospheric plasma. Modeling the interaction shows that the magnitude of the ULF wave electric field, e, and the geomagnetic field, B0, giving an e×B0 drift, is the dominant mechanism for changing the radio frequency. We also show how data from high frequency (HF) Doppler sounders can be combined with HF radar data to provide details of the spatial structure of ULF wave energy in the ionosphere. Due to spatial averaging effects, the spatial structure of ULF waves measured in the ionosphere may be quite different to that obtained using ground based magnetometer arrays. The ULF wave spatial structure is shown to be a critical parameter that determines how ULF wave effects alter the frequency of HF signals propagating through the ionosphere.